(untitled) - McMurry, John (Upper Saddle River, N.J., 2003)
Having secured the loyalty of both instructors and students, this best-selling, highly student-oriented text offers clear and concise use of language, thoughtful attention to problem-solving, and engaging discussions of relevant applications. Readable without sacrificing depth of content, it effectively covers the essentials of allied health chemistry without becoming bogged down in excessive and unnecessary detail, and puts chemistry in the context of everyday life. Maintaining interest and promoting student confidence, it offers a relaxed and friendly writing style that is highly accessible to the student with no scientific background and encourages analytic skill-building throughout with numerous problems, worked-out examples, and conceptual exercises.
Keywords: Chemistry,Hóa học